2012
DOI: 10.1007/s11748-012-0108-1
|View full text |Cite
|
Sign up to set email alerts
|

A case of intravenous leiomyomatosis of uterine origin, extending through the inferior vena cava to right atrium

Abstract: Intravenous leiomyomatosis (IVL) is a rare benign tumor that originates from uterus, and sometimes extends to the right heart. We report a case of IVL that extended to right atrium through the inferior vena cava (IVC) which was resected using partial cardiopulmonary bypass. Multi detector computed tomography and ultrasound played a vital role in arriving at the diagnosis. Complete resection of tumor in the heart and great vein, and separation of the tumor stump from the IVC are essential in the treatment of IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The features of malignant thrombosis are similar to those of the primary tumor and the lesion is generally considerably smaller than the IVL. In addition, malignant thrombosis is not associated with a history of uterine myoma or surgery for uterine myoma (10). Complete surgical excision of the tumor is an appropriate treatment option for IVL, and the final diagnosis is dependent on histopathological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The features of malignant thrombosis are similar to those of the primary tumor and the lesion is generally considerably smaller than the IVL. In addition, malignant thrombosis is not associated with a history of uterine myoma or surgery for uterine myoma (10). Complete surgical excision of the tumor is an appropriate treatment option for IVL, and the final diagnosis is dependent on histopathological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al have recently reviewed the literature and identified 200 reported cases of leiomyomatosis, 68 of which had intracardiac extension. 5 They identified signs of cardiac failure, venous obstruction or abdominal distension (in women with previous history of hysterectomy done for fibroid uterus) as being the most common mode of presentation in those with involvement of the right atrium as in our case. In the early stages of venous extension, the diagnosis is often unrecognized and further extension of intravenous leiomyomatosis is not prevented by resection of the primary tumour.…”
Section: Discussionmentioning
confidence: 54%
“…2 IVL may also embolise to the right cardiac chambers or pulmonary artery and cause obstruction .It may be diagnosed as a primary cardiac tumour or a venous thrombus. 5 Intra-venous leiomyomatosis, benign metastasizing leiomyoma and malignant leiomyosarcoma are three rare associated variants of uterine leiomyoma. Recognition of the potential of fibroids for venous invasion was accredited to Birch Hirschfeld who described four cases in 1896.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The features of malignant thrombosis are similar to those of the primary tumor and the lesion is generally considerably smaller than the IVL. In addition, malignant thrombosis is not associated with a history of uterine myoma or surgery for uterine myoma [18]. Complete surgical excision of the tumor is an appropriate treatment option for IVL, and the final diagnosis is dependent on histopathological analysis.…”
Section: Differential Diagnosismentioning
confidence: 99%